URGENSI KURIKULUM DAN SISTEM PEMBELAJARAN INKLUSIF GENDER - ZULAIHA, SITI (Universitas Islam Negeri Raden Intan Lampung, 2017)
AbstactUrgency curriculum and gender inclusive learning system because there are still many gaps in the world of education, especially in three aspects, namely access, participation and benefits and msih lack of participation of female learners in learning, low skill of women in technology mastery, there are still many curriculum and teaching materials that is bias gender and there is still a benefit gap in the curriculum and learning gained by male and female learners. It is the background of the importance of curriculum and gender inclusive learning. The curriculum and inclusive gender learning is a curriculum that integrates gender equality principles (taking into account equality of access, participation, control, benefits, and ensuring no gender discrimination in its various forms), or in curriculum documents in an attempt to achieve social justice. While gender-inclusive learning is learning that recognizes and considers the different needs, interests, experiences, and ways of learning of students and students caused by the construction of gender in their environment. Furthermore, to analyze the implementation of curriculum in gender inclusive learning the author presents the rubric of syllabus analysis and the rubric of analysis of learning implementation plan so that the implementation of learning is in accordance with the principles of gender equality.Keywords: Urgency Curriculum, Gender Inclusive Learning